Cancer-Associated Fibroblasts Promote the Upregulation of PD-L1 Expression Through Akt Phosphorylation in Colorectal Cancer - Gao, Yang; Sun, Zhao; Gu, Junjie; Li, Zhe; Xu, Xiuxiu; Xue, Chunling; Li, Xuechun; Zhao, Lin; Zhou, Jianfeng; Bai, Chunmei; Han, Qin; Zhao, Robert Chunhua (Frontiers in Oncology, 2021)
Upregulation of immune checkpoint proteins is one of the main mechanisms for tumor immune escape. The expression of programmed death ligand-1 (PD-L1) in colorectal cancer (CRC) is higher than in normal colorectal epithelial tissue, and patients with higher PD-L1 expression have a poorer prognosis. Additionally, PD-L1 expression in CRC is affected by the tumor microenvironment (TME). As a major component of the TME, cancer-associated fibroblasts (CAFs) can act as immune regulators and generate an immunosuppressive tumor microenvironment. Therefore, we speculated that CAFs may be related to the upregulation of PD-L1 in CRC, which leads to tumor immune escape. We found that CAFs upregulate PD-L1 expression in CRC cells through AKT phosphorylation, thereby reducing the killing of CRC cells by peripheral blood mononuclear cells. The ratio of CAFs to CRC cells was positively correlated with AKT phosphorylation and the expression of PD-L1 in CRC in vitro. Consistent with the in vitro results, high CAF content and high expression of PD-L1 were negatively correlated with disease-free survival (DFS) of CRC patients. These results indicate that the upregulation of PD-L1 expression in CRC by CAFs through the activation of Akt is one of the molecular mechanisms of tumor immune escape. Thus, targeted anti-CAF therapy may help improve the efficacy of immunotherapy.